2018
DOI: 10.4049/jimmunol.1800224
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Deficiency Suppresses the Release of IL-1β and IL-1α in Macrophages via a Type 1 IFN–Dependent Mechanism

Abstract: Obesity and diabetes modulate macrophage activation, often leading to prolonged inflammation and dysfunctional tissue repair. Increasing evidence suggests that the NLRP3 inflammasome plays an important role in obesity-associated inflammation. We have previously shown that activation of the lipotoxic inflammasome by excess fatty acids in macrophages occurs via a lysosome-dependent pathway. However, the mechanisms that link cellular lipid metabolism to altered inflammation remain poorly understood. PPARγ is a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…This can be stimulated by fatty acids as palmitate and may require mitochondrial ROS production (141,142). In line with this data, deletion of PPARγ in macrophages leads to a reduction IL-1β production and release in response to NLRP3 activators, an effect mediated by IFN-β (143). Thus, FAO and resultant metabolic byproducts play a complex role in the regulation of macrophage reparative and inflammatory functions.…”
Section: Lipid Metabolismsupporting
confidence: 62%
“…This can be stimulated by fatty acids as palmitate and may require mitochondrial ROS production (141,142). In line with this data, deletion of PPARγ in macrophages leads to a reduction IL-1β production and release in response to NLRP3 activators, an effect mediated by IFN-β (143). Thus, FAO and resultant metabolic byproducts play a complex role in the regulation of macrophage reparative and inflammatory functions.…”
Section: Lipid Metabolismsupporting
confidence: 62%
“…It is likely that the dysbiotic microbiome in the obesity and NAFLD patients may harbor persistent infections. In turn, through over-production of long-chain fatty acid (LFA) and leptin by expanding adipocytes, obesity is accompanied with general immune suppression including aberration of antiviral IFN signaling, which leads to high susceptibility to viral infections (Figure 3) [4,11,48,107,109]. Therefore, in most cases of infectobesity, obesity and viral infections may interact dynamically as a reciprocal causality rather than a simple sequential relationship of “chicken or the egg” [14].…”
Section: Interferon Responses Underlying the Reciprocal Causalitymentioning
confidence: 99%
“…In both preclinical and clinical studies, therapeutics that target the NLRP3 inflammasome and/or neutralize its primary product, IL‐1β, have been associated with improved wound healing, reduced atherosclerosis, and decreased severity of heart failure . We, and others, have demonstrated that excess fatty acids (FAs) can trigger inflammasome activation in macrophages in the setting of obesity and diabetes, the so‐called lipotoxic inflammasome . However, the molecular pathways that influence how FAs produce toxicity in macrophages and lead to this inflammatory response are not well understood.…”
Section: Introductionmentioning
confidence: 99%